Perbedaan Efektifitas Gaya Kepemimpinan Manajer Pria dan Wanita - Faniza Fitri, Aisyah; Sri Surwasih (Bandung Conference Series: Business and Management, 2023)
Abstract. This study aims 1) to determine the effectiveness of the leadership style of male managers at Rindang Farm. 2) to determine the effectiveness of the leadership style of female managers in Rindang Farm. 3) to find out the differences in leadership styles in Rindang Farm. The research method used is a quantitative method that is descriptive survey and operates the calculations using the SPSS 25.00 program. The variable in this research is leadership style. Collection of data obtained through questionnaires, observation, and literature study. The sampling technique is saturated sampling. The respondents of this research were 51 employees of Rindang Farm, West Sumatra. The results of this study concluded that 1) the effectiveness of the leadership style of male managers at the Rindang Farm farm in West Sumatra, was considered very effective. 2) the effectiveness of the leadership style of female managers at the Rindang Farm farm in West Sumatra, is considered very effective. 3) the effectiveness of the leadership style of male managers is more effective than the leadership style of female managers. Abstrak. Penelitian ini bertujuan 1) untuk mengetahui efektivitas gaya kepemimpinan manajer pria di Peternakan Rindang Farm. 2) untuk mengetahui efektivitas gaya kepemimpinan manajer wanita di Peternakan Rindang Farm. 3) untuk mengetahui perbedaan gaya kepemimpinan di Peternakan Rindang Farm. Metode penelitian yang digunakan adalah metode kuantitatif bersifat deskriptif survei dan mengoperasikan perhitungannya menggunakan program SPSS 25.00. Variabel dalam penelitian ini adalah gaya kepemimpinan. Pengumpulan data yang diperoleh melalui kuesioner, observasi, dan studi pustaka. Teknik penarikan sampel adalah sampling jenuh. Responden penelitian ini adalah karyawan Peternakan Rindang Farm Sumatra Barat yang berjumlah 51 orang. Hasil penelitian ini menyimpulkan bahwa 1) efektivitas gaya kepemimpinan menejer pria pada pertenakan Rindang Farm yang berada di Sumatra Barat, dinilai sangat efektif. 2) efektivitas gaya kepemimpinan menejer wanita pada pertenakan Rindang Farm yang berada di Sumatra Barat, dinilai sangat efektif. 3) efektivitas gaya kepemimpinan manejer pria lebih efektif dibandingkan dengan gaya kepemimpinan manejer Wanita.